Vocational Training and Youth Empowerment in Nigeria: Evidence from Informal Sector Operators’ Activity in Gombe Metropolis - Buba, Abdullahi; Somasundara, Jayakodi W Dayananda; Adamu, Idi; Samuel, Dorcas (American Journal of Social Sciences and Humanities, 2022)
This study was conducted to empirically examine the role of the informal sector in youths’ empowerment in Gombe metropolis. A structured questionnaire was used to gather first-hand information on variables of interest and both descriptive statistic and ordered logistic regression analysis were conducted to achieve the major and specific objectives of the study. The primary objectives of the study include to examine (i) how does Vocational training among informal sector operators influence youth empowerment in Gombe metropolis; (ii) how does customers' patronage of the informal sector's services influence youth empowerment in Gombe metropolis; and (iii) how does capital requirement among informal sector operators influence youth empowerment in Gombe metropolis. Empirical results obtained from the study indicated that Vocational training among informal sector operators has a positive and significant influence on the likelihood of youths empowerment in Gombe metropolis of Gombe state; customers' patronage, as well as capital requirements, were also found to have a positive and significant influence on youths’ empowerment in Gombe metropolis; and all the control variables included in the model (except gender) also have positive and significant probability on youth empowerment in Gombe metropolis. We conclude by presenting concluding remarks and policy implications for decision-making toward repositioning technical and vocational education in Nigeria to effectively curb incessant overdependence on the government for job creation in Nigeria.